An energy criterion to predict delayed failure of multi-directional polymer matrix composites based on a non-linear viscoelastic model - Rui Miranda Guedes (2004)
The life-time prediction of multi-directional polymer composite under creep loading is proposed and assessed. Energy failure criterion, based on the theoretical developments of Reiner and Weissenberg, is modified and incorporated into a computer program called LAMFLU. This algorithm was developed to predict the long-term behavior of viscoelastic polymer matrix composite laminates. In the present theoretical model, failure is part of the complete constitutive description of the material. The laminate failure prediction is based on the last ply failure; each ply failure promotes a stiffness degradation related with the failure mode. The quality of theoretical predictions is good compared with published experimental results.